2001
DOI: 10.2337/diabetes.50.8.1714
|View full text |Cite
|
Sign up to set email alerts
|

A Preprandial Rise in Plasma Ghrelin Levels Suggests a Role in Meal Initiation in Humans

Abstract: The recently discovered orexigenic peptide ghrelin is produced primarily by the stomach and circulates in blood at levels that increase during prolonged fasting in rats. When administered to rodents at supraphysiological doses, ghrelin activates hypothalamic neuropeptide Y/agouti gene-related protein neurons and increases food intake and body weight. These findings suggest that ghrelin may participate in meal initiation. As a first step to investigate this hypothesis, we sought to determine whether circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

104
1,749
15
67

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,593 publications
(1,956 citation statements)
references
References 37 publications
104
1,749
15
67
Order By: Relevance
“…Leptin concentration gradually rose throughout the day, with small declines immediately after each meal, and reached a zenith roughly during the middle of the sleep period. Ghrelin followed the same pattern (Figure 8), except for the pronounced surges immediately prior to a meal, followed by equally dramatic declines immediately after the meal (Cummings et al, 2001). Because the meals were provided at known, fixed times, this evidence supports the hypothesis that the surge in ghrelin secretion prior to meals is a cephalic phase response that serves to initiate feeding and/or to prepare the person to digest and metabolize food.…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?supporting
confidence: 63%
See 3 more Smart Citations
“…Leptin concentration gradually rose throughout the day, with small declines immediately after each meal, and reached a zenith roughly during the middle of the sleep period. Ghrelin followed the same pattern (Figure 8), except for the pronounced surges immediately prior to a meal, followed by equally dramatic declines immediately after the meal (Cummings et al, 2001). Because the meals were provided at known, fixed times, this evidence supports the hypothesis that the surge in ghrelin secretion prior to meals is a cephalic phase response that serves to initiate feeding and/or to prepare the person to digest and metabolize food.…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?supporting
confidence: 63%
“…In human volunteers provided meals on a fixed schedule, plasma ghrelin concentration displayed a consistent pattern of being low immediately after a meal, slowly increasing, and then having a rapid increase in concentration immediately prior to the next meal (Cummings et al, 2001; Figure 7). The pattern of ghrelin concentration was roughly opposite to the pattern of insulin concentration, but in phase with the circadian cycle of leptin concentration, though much more variable than leptin concentration.…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?mentioning
confidence: 95%
See 2 more Smart Citations
“…For instance, ghrelin is known to be influenced by meals in man 26. Nevertheless, on 24‐hour serial assessment of circulating ghrelin concentrations in humans, it was shown that samples taken before breakfast correlated strongly with 24‐hour integrated area under the curve values ( r  = 0.873), suggesting that a single starved morning sample could be used as a surrogate for 24‐hour profiles to estimate overall ghrelin concentrations 27. Therefore, to minimize the effects of daily ghrelin dynamics in this study, all cat samples were taken in the early morning and before food.…”
Section: Discussionmentioning
confidence: 99%